Reseliensi Perempuan Eks-HTI terhadap Ideologi Pancasila Di Kediri - Mahfudhotin; Ahmad Khoirul Mustamir, (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study considers ex-HTI women who play a role in spreading the ideology of their organization. At the same time, women openly state that Pancasila and democracy are products of Western thought. So, it is very important to implement khilafah in the nation and state kaffah. This understanding has its own problems after the issuance of PERPU No. 2 of 2017 concerning Community Organizations which is the basis for the dissolution of HTI. In this context, with a qualitative research method from the perspective of the women's movement, it is intended to find out about the basic understanding of former HTI women in Kediri City towards their ideology and Pancasila after the issuance of PERPU No. 2 of 2017 concerning Community Organizations. In addition, this study seeks answers to the riseliency pattern of ex-HTI women in Kediri City after PERPU No. 2 of 2017 concerning Community Organizations. By using the method of interviews, documentation and observation, the results of the study found that the foundation of the basic understanding of the former HTI women of Kediri City follows the ideological doctrine of the organization. In its existence, it does not have a big impact after the issuance of PERPU No. 2 of 2017 concerning Community Organizations. They strengthen and spread ideology through recitations in the community and outside the community. the strategies used, do not use jargon that shows HTI. The enactment of PERPU No. 2 of 2017 concerning Community Organizations has no significant effect on the killing of HTI ideology in Kediri City.